2006
DOI: 10.1160/th05-05-0361
|View full text |Cite
|
Sign up to set email alerts
|

Improved coagulation in bleeding disorders by Non-Anticoagulant Sulfated Polysaccharides (NASP)

Abstract: SummaryAdditional therapeutic options are needed for patients with bleeding disorders such as hemophilia A, hemophilia B, severe von Willebrand disease, and other rare factor deficiencies. A novel approach to improve coagulation in such clotting disorders has been identified that, parodoxically, involves heparinlike sulfated polysaccharides.Select molecules of this broad class are largely devoid of anticoagulant activity and are here denoted Non-Anticoagulant Sulfated Polysaccharides (NASPs).A mechanism involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
61
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 46 publications
1
61
0
Order By: Relevance
“…Fucoidan, a sulfated polysaccharide from a brown seaweed, decreases bleeding time and clotting time in hemophilia (8,9). Decreased bleeding times in the hemophilia animal models by in vivo administration of fucoidan highlights the beneficial FIGURE 4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fucoidan, a sulfated polysaccharide from a brown seaweed, decreases bleeding time and clotting time in hemophilia (8,9). Decreased bleeding times in the hemophilia animal models by in vivo administration of fucoidan highlights the beneficial FIGURE 4.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vitro studies by using platelet poor plasma from hemophilia animal models and human patients have showed that fucoidan inhibits tissue factor pathway inhibitor, thereby contributing to an increase in the extrinsic coagulation pathway activity (8). The effect of fucoidan on platelets, however, has not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are believed to act through blockade of tissue factor pathway inhibitor, effectively removing the brakes from coagulation. NASP can accelerate the clotting times of plasma from hemophilia patients [11]. Finally, missense mutations leading to premature stop codons in FVIII or FIX occur in approximately 10% to 15% of persons with hemophilia A or B, respectively.…”
mentioning
confidence: 99%